2017
DOI: 10.1159/000480241
|View full text |Cite
|
Sign up to set email alerts
|

SLC2A1 Tag SNPs in Greek Patients with Diabetic Retinopathy and Nephropathy

Abstract: Backround: Genetic variants are implicated in the development of diabetic retinopathy (DR) and nephropathy (DN). The role of solute carrier family 2-facilitated glucose transporter member 1 (SLC2A1), also known as glucose transporter (GLUT1), on DR and DN remain controversial. Objective: Examination of the influence of tag SLC2A1 single-nucleotide polymorphisms (SNPs) on the development of DR and DN during the course of type 2 diabetes mellitus (T2DM). Methods: A total of 169 patients with DR or DN, 107 uncomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…SLC2A1 XbaI (rs841853) also fails to show any association with diabetic retinopathy in Chinese patients with type 2 DM 29. In contrast, Siokas et al30 reported that the tag SLC2A1 polymorphism is associated with diabetic retinopathy and DN in Greek patients with type 2 DM. Roy et al31 also showed that the SLC2A1 polymorphism is associated with the progression of diabetic retinopathy in African-Americans with type 1 DM.…”
Section: Discussionmentioning
confidence: 95%
“…SLC2A1 XbaI (rs841853) also fails to show any association with diabetic retinopathy in Chinese patients with type 2 DM 29. In contrast, Siokas et al30 reported that the tag SLC2A1 polymorphism is associated with diabetic retinopathy and DN in Greek patients with type 2 DM. Roy et al31 also showed that the SLC2A1 polymorphism is associated with the progression of diabetic retinopathy in African-Americans with type 1 DM.…”
Section: Discussionmentioning
confidence: 95%
“…The solute carrier family 1 – glial affinity glutamate transporter-member 2 (SLC1A2) gene, [also known as Excitatory amino acid transporter 2 (EATT2) or glutamate transporter 1 (GLT-1)], encodes SLC1A2, a member of the group of solute transporter proteins [ 45 ]. Elevated levels of glutamate in the synaptic cleft and extracellularly are neurotoxic and have been associated with neurodegeneration.…”
Section: Resultsmentioning
confidence: 99%
“…However, only a few genetic reports support possible pleiotropy between DN and DR 16 17 34 35. Hosseini et al 36 tested previous suggestive signals for DN for association with severe DR, but none of the loci showed a significant association after multiple testing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, genetic loci with pleiotropic effects, whereby one genetic locus can affect more than one phenotype, may underlie the association between DR and DKD phenotypes 15. However, to date only a few genetic polymorphisms have been reported to be associated with these two complications, including interleukin (IL)-1016 and SLC2A1 17…”
Section: Introductionmentioning
confidence: 99%